1998
DOI: 10.1164/ajrccm.157.6.9609040
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Epidermal Growth Factor and Epidermal Growth Factor Receptor Immunoreactivity in the Asthmatic Human Airway

Abstract: Chronic airway inflammation, one of the pathophysiologic features of bronchial asthma, is suspected to be responsible for irreversible pathological changes of airways, called airway remodeling. To examine the mechanisms of airway remodeling in asthma, we investigated the expression of epidermal growth factor (EGF) and its receptor immunohistochemically in asthmatic human airways. Airway specimens from seven patients with asthma were obtained from autopsied and surgically resected lungs. Control specimens were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
158
0
5

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(173 citation statements)
references
References 26 publications
10
158
0
5
Order By: Relevance
“…Amishima et al (1998) also reported increased expression of EGF and EGFR in asthmatic human airway epithelium compared with their levels in a control population, suggesting that EGF may contribute to the pathophysiology of bronchial asthma. EGF and eosinophilderived TGF-, another natural ligand for the EGFR, have been shown to stimulate MUC5AC mucin gene expression and protein synthesis in a human airway epithelial cell line, and goblet cell metaplasia (Burgel and Nadel, 2004).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Amishima et al (1998) also reported increased expression of EGF and EGFR in asthmatic human airway epithelium compared with their levels in a control population, suggesting that EGF may contribute to the pathophysiology of bronchial asthma. EGF and eosinophilderived TGF-, another natural ligand for the EGFR, have been shown to stimulate MUC5AC mucin gene expression and protein synthesis in a human airway epithelial cell line, and goblet cell metaplasia (Burgel and Nadel, 2004).…”
Section: Discussionmentioning
confidence: 86%
“…Pretreatment with gefitinib inhibits the activation of EGFR and Akt, reduces the release of Th2 cytokines from airway epithelium, and decreases the recruitment of eosinophils into airway epithelium. In fact, EGFR expression is increased in bronchial epithelium in adult and childhood asthma and there is an increasing number of studies using EGFR to regulate airway inflammation in asthma (Amishima et al, 1998;Polosa et al, 2002;Fedorov et al, 2005). However, it is not well known the mechanisms that EGFR tyrosine kinase inhibitor inhibits allergic airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the EGFR signaling pathway is implicated in airway biology and EGFR is expressed by many cell types in the lung, including smooth muscle cells, endothelium, fibroblasts and epithelium [3,4]. Human asthmatic airways show increased EGFR immunoreactivity in airway epithelium, glands, and smooth muscle [5] and EGFR activation has been reported to promote epithelial repair and to induce mucin production and remodeling of airway tissues [6,7]. We previously reported that multiple OVA challenges increased protein expression of the EGFR ligand, heparin-binding EGF-like growth factor (HB-EGF) in airway epithelium in Brown Norway (BN) rats [4].…”
Section: Introductionmentioning
confidence: 99%